DEFORESTASI SEBAGAI PELANGGARAN FIQH ALBI’AH PERSPEKTIF YUSUF AL-QARADAWI - Saipul Nasution; Muhammad Azrul Amirullah; ‘Ilma Tsaqila Khoirun Nisa; Andini Rachmawati (Universitas Kiai Abdullah Faqih Gresik, 2026)
This study aims to analyze the phenomenon of unemployment from the perspective of human resource development based on Islamic values, specifically through the maqasid al-shari’ah approach. Conventional development models focused solely on economic growth often fail to comprehensively address unemployment issues because they neglect the dimensions of ethics, social justice, and spirituality. This study employs a qualitative method using a literature review approach, examining various classical and contemporary works related to Islamic economics and human development. The findings indicate that unemployment is not merely an economic issue but also reflects a failure in the holistic management of human resources. From the perspective of the maqasid al-shari’ah, development must be directed toward the protection of religion, life, intellect, lineage, and wealth, which implicitly demands the creation of fair, productive, and dignified employment opportunities. Therefore, a reconstruction of development policies is necessary one that focuses not only on macroeconomic indicators but also on the comprehensive enhancement of human quality. This study is expected to provide a conceptual contribution to the development of public policies based on Islamic values to address unemployment in a sustainable manner.